2019
DOI: 10.1089/heq.2018.0036
|View full text |Cite
|
Sign up to set email alerts
|

Psychosexual Consequences of Female Genital Mutilation and the Impact of Reconstructive Surgery: A Narrative Review

Abstract: Purpose: We aim to provide a comprehensive overview of the health consequences of female genital mutilation/cutting (FGM/C), with a particular focus on the psychosexual implications of this practice and the overall impact of reconstructive plastic surgery.Methods: A MEDLINE search through PubMed was performed to identify the best quality evidence published studies in English language on long-term health consequences of FGM/C.Results: Women with FGM/C are more likely to develop psychological disorders, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 55 publications
2
41
0
Order By: Relevance
“…Similarly, the reviewed studies equally established that FGM entails psychological, psychosocial, and psychosexual effects, although there is a few quality evidence to adequately back it [49]. Some studies identified effects such as anxiety, post-traumatic disorder, and depression, perhaps as a result of shame arising from social victimization [38].…”
Section: Consequences Of Female Genital Mutilation In Africamentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the reviewed studies equally established that FGM entails psychological, psychosocial, and psychosexual effects, although there is a few quality evidence to adequately back it [49]. Some studies identified effects such as anxiety, post-traumatic disorder, and depression, perhaps as a result of shame arising from social victimization [38].…”
Section: Consequences Of Female Genital Mutilation In Africamentioning
confidence: 99%
“…This study commensurates the findings from a narrative review of psychosexual consequences and a meta-analysis study on Nigerian women based on their psychosocial analysis. The former posited that women with FGM are more prone to developing psychological disorders such as phobia, anxiety, somatization, self-esteem, and post-traumatic stress disorder and equally physiological problem in respect to being sexually stimulated, while the latter revealed that FGM creates psychological problems, sexual abnormalities, and unhappiness in marriage [48,49].…”
Section: Consequences Of Female Genital Mutilation In Africamentioning
confidence: 99%
“…Although many authors uphold the negative sexual and physical impact of FGM/C, research focused on the correlates of psychopathology and FGM/C is still in its nascent stages [17]. Most commonly identified manifestations of psychological impairments include negative self-image, depression, anxiety, somatization, and posttraumatic stress disorder [17][18][19][20][21][22][23][24]. In a recent comprehensive literature review, 14 of the 16 included studies reported an association between FGM/C and at least one adverse mental health outcome [25].…”
Section: Introductionmentioning
confidence: 99%
“…Different options for reconstruction of the female genital after FGM/C have been proposed, such as defibulation, removal of cysts, reconstruction of clitoris and labia, neuromas, and scar tissue, although clitoral reconstruction (CR) has been the most widely used [24,26]. CR has been shown to improve both genital anatomy and sexual function, including favorable changes in genital self-image [10,[27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation